The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11095-008-9788-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Terpenoids and Flavonoids from Ginkgo Biloba Extract Induce the Expression of Hepatic Drug-Metabolizing Enzymes Through Pregnane X Receptor, Constitutive Androstane Receptor, and Aryl hydrocarbon Receptor-Mediated Pathways

Abstract: Purpose-The objective of the current study is to investigate the hypothesis that bioactive terpenoids and flavonoids of Ginkgo biloba extract (GBE) induce human hepatic drug metabolizing enzymes (DMEs) and transporters through the selective activation of pregnane X receptor (PXR), constitutive androstane receptor (CAR), and aryl hydrocarbon receptor (AhR). Methods-Human primary hepatocyte (HPH), and HepG2 cells are used as in vitro models for enzyme induction and nuclear receptor activation studies. A combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
92
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 43 publications
16
92
2
Order By: Relevance
“…Consistent with these findings, G. biloba extract is capable of inducing PXR target genes (Table II), including CYP3A4, as shown in PXR-expressing LS180 cells in culture (41) and in primary cultures of human hepatocytes (42). Although ginkgolide A and B have been reported to activate human PXR (42,43), the concentrations used in those cell culture experiments far exceed the levels present in an extract of G. biloba. Thus, it remains to be determined which chemical constituent(s) is responsible for the in vitro activation of PXR by G. biloba extract.…”
Section: Ginkgo Bilobasupporting
confidence: 68%
See 1 more Smart Citation
“…Consistent with these findings, G. biloba extract is capable of inducing PXR target genes (Table II), including CYP3A4, as shown in PXR-expressing LS180 cells in culture (41) and in primary cultures of human hepatocytes (42). Although ginkgolide A and B have been reported to activate human PXR (42,43), the concentrations used in those cell culture experiments far exceed the levels present in an extract of G. biloba. Thus, it remains to be determined which chemical constituent(s) is responsible for the in vitro activation of PXR by G. biloba extract.…”
Section: Ginkgo Bilobasupporting
confidence: 68%
“…Detailed dose-response data indicate that the extract is effective in activating human PXR transcriptional activity at concentrations of 100-800 µg/ml (Table I). Activation of human PXR by G. biloba extract was confirmed in a subsequent study (42) ( Table I). Consistent with these findings, G. biloba extract is capable of inducing PXR target genes (Table II), including CYP3A4, as shown in PXR-expressing LS180 cells in culture (41) and in primary cultures of human hepatocytes (42).…”
Section: Ginkgo Bilobasupporting
confidence: 53%
“…First, the study does not rule out the possibility of induction of MPA metabolism by G. biloba. A recent study showed that G. biloba and its components induce cytochrome P450 enzymes, transporters, and UGT1A1 (Li et al, 2009). The effect of G. biloba on MPA-metabolizing enzymes in hepatocytes warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…However, CYP1B1 is uniquely overexpressed in a wide range of human cancers of different histogenetic types compared to normal tissues (26)(27)(28). Several studies reported that the Ginkgo biloba extract exhibits differential induction of CYPs (29)(30)(31). The aim of this study was to assess whether the Ginkgo biloba extract induces CYP1B1 expression and affects the proliferation of MCF-7 and MDA-MB-231 human breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%